A New Device for Thoracoscopic Cryoanalgesia in Pectus Excavatum Repair: Preliminary Single Center Experience - Torre, Michele; Mameli, Leila; Bonfiglio, Rachele; Guerriero, Vittorio; Derosas, Lucia; Palomba, Loredana; Disma, Nicola (Frontiers in Pediatrics, 2021)
Introduction Cryoanalgesia has been recently described as alternative technique for immediate and persistent pain treatment after pectus excavatum repair. Cryoanalgesia has the potentiality to reduce analgesic consumption and length of hospitalization. However, cryoanalgesia has not been standardized yet: the previous reports describe different techniques and systems and incude only small series. In Europe, no reports on cryoanalgesia for pectus repair have been published so far. Matherials and Methods This is a prospective single centre pilot study performed in adolescents undergoing minimally invasive pectus excavatum repair with a new cryoanalgesia system, using a probe designed specifically for thoracoscopy. This new double lumen probe has the theoretical advantage of freezing only in its tip, so reducing the risk of complications. Results Seven patients undergoing pectus excavatum repair were treated with cryoanalgesia performed with the new probe. No complications of cryoanalgesia were reported. Total consumption of morphine during hospital stay was between 0,1 and 0,35 mg/kg, with no side effects reported. Mean time to discharge was 2.4 days. All patients reported a good pain control with a fair need of rescue medications for pain relief during the first week after discharge, and a very good pain control without need of rescue medications during following weeks. Conclusions Our pilot study showed that the new cryoanalgesia system is efficacious in terms of pain control, hospital stay and resumption of post-operative activities.The cryoprobe designed allowed an easy and safe maneuver. A prospective trial is needed to better define the risks and benefits of this technique.